2021
DOI: 10.1177/08465371211008649
|View full text |Cite
|
Sign up to set email alerts
|

Which Aspects of the CanMEDS Competencies are Most Valued in Radiologists? Perspectives of Trainees From Other Specialties

Abstract: Purpose: Radiologists work primarily in collaboration with other healthcare professionals. As such, these stakeholder perspectives are of value to the development and assessment of educational outcomes during the transition to competency-based medical education. Our aim in this study was to determine which aspects of the Royal College CanMEDS competencies for diagnostic radiology are considered most important by future referring physicians. Methods: Institutional ethics approval was obtained. After pilot testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…6,[14][15][16] Appropriate assessment of non-"Medical Expert" CanMEDS roles is integral as it has been previously demonstrated that other specialties most value aptitude in the "Communicator" and "Professional" roles among residents. 17 Dedicated professional development opportunities for faculty not only to further develop assessment but also to further develop teaching of non-"Medical Expert" CanMEDS roles may thus be of benefit in the transition to CBD. 15,16 Our observations of participants' perceived impact of the transition to CBD on their PGME training suggests additional work is required to ensure that residents are aware of their roles.…”
Section: Discussionmentioning
confidence: 99%
“…6,[14][15][16] Appropriate assessment of non-"Medical Expert" CanMEDS roles is integral as it has been previously demonstrated that other specialties most value aptitude in the "Communicator" and "Professional" roles among residents. 17 Dedicated professional development opportunities for faculty not only to further develop assessment but also to further develop teaching of non-"Medical Expert" CanMEDS roles may thus be of benefit in the transition to CBD. 15,16 Our observations of participants' perceived impact of the transition to CBD on their PGME training suggests additional work is required to ensure that residents are aware of their roles.…”
Section: Discussionmentioning
confidence: 99%